PENINGKATAN HASIL BELAJAR SISWA KELAS IX DENGAN PEMBELAJARAN STAD PADA BANGUN RUANG SISI LENGKUNG TABUNG DI MTs. SA MIFTAHUL HUDA - Abd. Rahman S (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
This study investigated how STAD strategy could be implemented to enhance the students’ mathematics achievement on the concept of the shape of thecylinder curvature facefor the first semester students in grade IX,MTs. SA Miftahul Huda Mayangan, in the academic year 2014/2015. The research design adopted for this study is classroom action research (CAR)consisted two cycles. The data collection for this action research study took many forms; observation, interview, test, and documentation. The result of data analysis on cycle 1 showed that the students’ score after altering into percentage gained only 76%. It was very small percentage to fulfill the criterion of minimum completeness (KKM) 75%. Based on the result on the first cycle, it was necessary for the researcher to conduct the next cyclical procedure. In cycle 2,the percentage of the students’ score was significantly increased. It was derived 88%.Accordingly, it proved that the target of CAR success could finally be achieved. Therefore, the next action could be stopped.Keywords: STAD, area of shape, students’ achievement.